(untitled) (International Journal of Biology and Chemistry, 2026)
Steam methane reforming (SMR) remains the dominant industrial route for large-scale hydrogen production due to its technological maturity and economic competitiveness. However, conventional SMR is associated with significant carbon dioxide emissions, limiting its sustainability in the context of global decarbonization goals. This study presents a comprehensive process modeling and analysis of hydrogen production via SMR integrated with the water–gas shift reaction (WGSR) and post-combustion CO₂ capture. A detailed steady-state model was developed using Aspen HYSYS to evaluate mass and energy balances, hydrogen yield, and purification performance. The modeled process reflects an industrially relevant SMR–WGSR configuration and is assessed in the context of blue hydrogen production. In addition, a location-based feasibility analysis is conducted for Kazakhstan, identifying the Atyrau region as a favorable deployment site due to existing natural gas infrastructure and industrial integration potential. The results demonstrate high hydrogen purity (>97%) and confirm that integration of CO₂ capture significantly reduces carbon intensity while preserving process efficiency, supporting SMR with carbon capture as a viable transitional hydrogen technology. Keywords: Steam methane reforming; Hydrogen production; Water–gas shift; Blue hydrogen; Aspen HYSYS; Carbon capture